Zmiana wydajności studni głębinowych na przykładzie centralnego ujęcia wody dla Zielonej Góry = The variation of the efficiency of wells in the central water intake in Zawada near Zielona Góra - Hudak, Magda (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In article taken the variation of the efficiency of wells in the Central Water Intake in Zawada near Zielona Góra. This problem is very interesting in view of 35 years four galleries of wells went in this area and observed different time theirs work, ranged from 6 to 20 years. Two galleries, II and III, were analysed.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); wydajność; studnie; starzenie się studni; efficiency; wells; ageing of wells